Outcome of vital pulp therapy, revascularization, and apexification procedures: A retrospective study - Mey A Al-Habib (Wolters Kluwer Medknow Publications, 2022)
Introduction: Vital pulp therapy (VPT), revascularization, and apexification are different endodontic treatment modalities that aim to preserve tooth structure and decrease bacterial leakage increasing the long-term success of the treatment. The study aims to report the outcome of VPT, revascularization, and apexification procedures treated teeth in the endodontic department at King Abdulaziz University Dental Hospital performed by faculty and postgraduate residents. Materials and Methods: Thirty-three cases of VPT, revascularization, and apexification cases were evaluated. The outcome was assessed depending on the patient's signs and symptoms, healing of the apical periodontitis, and the signs of continued root development. Results: The overall results have shown that 60% of the cases were healed completely, 30% presented with incomplete healing, and 10% failed during the follow-up period and required further intervention. Conclusion: It has been concluded that the outcomes of VPT, revascularization, and apexification were fairly high as they favored healing of periapical periodontitis and root maturation with presentation of no signs and symptoms.